Bid-Ask Spreads, Trading Networks, and the Pricing of Securitizations - Hollifield, Burton; Neklyudov, Artem; Spatt, Chester (Review of Financial Studies, 2017)
The Financial Industry Regulatory Authority began collecting transaction data from broker-dealers in 2011 as a step toward enhancing its understanding of securitization markets. We use transaction data to document the importance of the interdealer network structure to market quality. Some dealers are relatively central in the network and trade with many dealers, while others are peripheral. Core dealers receive relatively lower and less dispersed spreads than peripheral dealers. We develop a model in which core and peripheral dealers trade with different customer clienteles and argue that the presence of relatively sophisticated customers in securitization markets explains these facts. Received June 23, 2015; editorial decision December 20, 2016 by Editor Andrew Karolyi.